Systemic iodine levels increase with povidone-iodine irrigation, but does this affect thyroid functions? A case-control study - Mehmet Batu Ertan; Kerem Başarır; Hakan Kocaoğlu; Mehmet Yağız Ayduğan; Erdal Güngör (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Background Intraoperative irrigation with diluted povidone iodine (PI) can be used to reduce the incidence of infection-related complications in arthroplasty surgeries. Since PI is associated with many interventions, especially skin antisepsis, its systemic effects are being studied. The aim of our study is to evaluate the systemic effects of PI, which we use as an irrigation solution, by means of urine iodine and thyroid function tests. Methods In this case-control study, 96 patients who underwent knee or hip arthroplasty were included and divided into two groups according to the irrigation solution. In the first group, PI was added to the standard irrigation. The second group was considered as the control group and only standard irrigation was applied. Urine iodine, thyroid stimulating hormone, free T3 and free T4 values were compared in the preoperative and postoperative periods of these two groups. In this way, the effect of absorbed iodine on thyroid functions was investigated. Results In the diluted PI group, urinary iodine levels were measured at maximum levels (450 µg/L) in the early postoperative period in most of the patients. The statistically significant difference in urinary iodine levels between the PI group and the control group, which started in the early postoperative period, continued until the last follow-up on the 14th postoperative day. In terms of thyroid functions, the observed differences were not statistically significant. Conclusion Studies to reduce periprosthetic infection show that PI can be preferred for irrigation before the closure of the joint area in total joint arthroplasty. Although the success of this treatment in periprosthetic infection has been investigated, its systemic examination has not been demonstrated. It was determined that PI treatment, which was seen to decrease in the systemic circulation within 14 days, did not show a statistically significant change in terms of thyroid functions when used at the determined concentration and duration. These results should be evaluated with larger and longer-term studies. Trial registration Clinical trials ID no. NCT05599841.